Development of Teaching Module Devices Using A Differentiated Approach with An Inquiry-Based Learning Model in the Motion Kinematics Material - Mamonto, Siti Nurhaliza; Buhungo, Trisnawaty Junus; Setiawan, Dewa Gede Eka; Supartin (Jurnal Pijar Mipa, 2024)
This study aims to describe the feasibility of independent curriculum teaching modules implemented with a differentiated approach with inquiry-based learning models in a diversified learning environment and accomplish specific criteria for utilization to attain student learning outcomes. This research was carried out at SMA Negeri 1 Passi class XI-A Physics. This research uses the type of R&D (Research & Development) with a 4D development model (Define, Design, Development, and Disseminate) by Thiagarajan. Validity testing uses a validation worksheet during the expert appraisal development phase. The results of this study show that the validation of all learning tools obtained 86% to 88% in "valid" criteria, and it can be concluded that the teaching module devices developed were valid.